Coupled Newmark seismic displacement analysis of cohesive soil slopes considering nonlinear soil dynamics and post-slip geometry changes - Ji, Jian; Lin, Zuojia; Li, Sikan; Song, Jian; Du, Shigui (Computers and geotechnics, 2024)
In geotechnical earthquake engineering, the seismic displacement is regarded as a more balanced index to explain the co-seismic performance of soil slopes. The Newmark’s sliding block theory is usually adopted to fast estimate the seismic slope displacement, and subject to different assumptions of the sliding soil mass, various improvements can be made onto the Newmark’s sliding block models. In this paper, the Newmark’s sliding block model is further modified to calculate the seismic displacement of shallow slopes composed of cohesive soils. The research significance is highlighted by several novel considerations: (1) the yield acceleration of translational sliding soil column derived from infinite slope model is modified to be displacement-dependent and is analytically expressed by simulating the seismic strain-softening effect of the undrained soil shear strength; (2) subjected to rotational sliding mode, the slope yield acceleration is further modified to reflect the change of slip surface geometries in the course of co-seismic downward slope movement; and (3) the seismic slope displacement model fully considers the flexibility of the soil mass by simulating the nonlinear dynamic vibration response of flexible soil columns, which is further coupled within the Newmark’s sliding block model. Verifications of the proposed modelling procedure were made by seismic displacement analysis of several numerical examples against strong earthquake records provided by NGA-West2. The comparison results calculated from different models show that ignoring the dynamic characteristics of the slope yield acceleration will underestimate the seismic slope displacement to some extent, which is undesirable in geotechnical risk management.